Strategies employed by EFL teachers at a Vocational High School for selecting appropriate English textbook - Maftukah, Siti; Astuti, Puji (ELT Forum: Journal of English Language Teaching, 2021)
Textbook is a tool which functions as a manual instruction in any branch of study included in language learning. Therefore, teachers should select an appropriate English textbook to support the learning activity because it have a big influence in the learning process. This study is about strategies of EFL teachers at a vocational high school in Semarang for selecting appropriate English textbook. The main purpose of this study was to investigate teachers’ strategies in selecting appropriate English textbook and dr. This study drew from the teachers regarding their criteria in selecting appropriate English textbook. Hence, this is a qualitative study that investigate the EFL teachers as the subjects. In collecting the data, we used open ended interview, questionnaire, and document analysis checklist. This study eployed theory of Garinger (2002) and BNSP by Permendikbud (2013) to analyse the data in order to know the strategies and the criteria used by the teachers in selecting appropriate English textbook. Based on the interview and the questionnaire, the finding showed there are some strategies in selecting appropriate textbook: teacher matched the textbook with the 2013 curriculum, read the KI, KD, Syllabus and learning objective. The data showed that all teachers select textbook based on their chosen, so that they were free to choose their textbook to support learning activity. However, some teachers select textbook by involving administrator and head school. There are also some textbook criteria there are: considering the goals and curriculum, textbook series, learning objective in the textbook, the age and background of the students, the availability and the effective cost. Based on the document analysis checklist, this research showed that the criteria of appropriate textbook in line with the Garinger (2002) and 2013 curriculum aspects based on BNSP. Next, the teachers also considered about the price of the textbook that must be cost effective and the textbook is easy to obtain. We argue that the identified strategies and criteria can be used as a consideration by English teachers to selectan appropriate English textbook.